A World of Peace Under the Rule of Law: The View from Europe - Christoph J. M. Safferling (Washington University Global Studies Law Review, 2007)
The topic which has been entrusted to me, A World of Peace Under the Rule of Law —The View from Europe, carries quite a heavy burden. Sixty years after the end of the Nürnberg Trials, this invitation to discuss a global rule of law demonstrates a substantial amount of trust in the German people, who come from a country where the Nazis had abolished every democratic principle and eliminated all individual liberties by dissolving the separation of power. Although sixty years is a long time in the case of our individual lives, the recent discussion about a German military contribution to the enforcement of Security Council Resolution 1701,2 and the deployment of German troops to the Middle East region as part of the United Nations Interim Force in Lebanon (UNIFIL) engagement, demonstrates that in the context of international relations, sixty years is but a short moment, like the blink of an eye. Taking all this into account, I will endeavour to reflect on the experiences and lessons learned, or not learned, from the past sixty years from a German’s viewpoint.
Keywords: Rule of law -- European Union countries; Peace; Democracy; Human rights; International offenses; Rule of law; Sovereignty; European Union; International